A smart indwelling needle with on-demand switchable anticoagulant and hemostatic activities. Issue 4 (2nd January 2020) - Wu, Yuanhao; Wang, Hongbo; Fan, Chuanchuan; Xu, Ziyang; Liu, Bo; Liu, Wenguang
Abstract : Herein, a novel concept is proposed for engineering a smart indwelling needle with on-demand switchable anticoagulant and hemostatic activities. Abstract : The repeated puncture of vessels with a conventional syringe needle causes frequent pain and fear in patients and particularly increases the risk of infections. An indwelling needle implanted in veins for a long time can avoid repeated punctures. However, blood coagulation during implantation and bleeding after the withdrawal of the needle are still key problems. Herein, we present a novel strategy to engineer a smart indwelling needle with on-demand switchable anticoagulation and hemostatic activities by modifying the outer surface and the inner surface of the indwelling needle with a coagulant catechol-functionalized chitosan coating and anticoagulant magnetic FeNP–dopamine-conjugated heparin (FeNP–HepDA), respectively. The smart indwelling needle is implanted into a rabbit's ear vein. Remarkably, under a magnetic field, the FeNP–HepDA-coated cannula inner wall maintains excellent anticoagulation activity, ensuing the patency of the needle due to the firm fixation of FeNP–HepDA. Upon removing the magnetic field, FeNP–HepDA can be shed. Under this condition, the cannular inner surface loses anticoagulation activity and when the needle is extracted from the vein, the hemostatic CHCS coating on the external surface serves to prevent bleeding. The strategy reported in this study opens up an avenue for designing biomaterials and biodevices exhibiting the coexistence of anticoagulation and coagulation.